2016
DOI: 10.1536/ihj.15-352
|View full text |Cite
|
Sign up to set email alerts
|

Troponin-I Level After Major Noncardiac Surgery and Its Association With Long-Term Mortality

Abstract: SummaryIndividuals with intermediate to high cardiac risk for major noncardiac surgery suffer from perioperative myocardial ischemic injury. The purpose of this study was to evaluate the long-term impact of postoperative cardiac troponin elevation on clinical outcome after major noncardiac surgery.Patients (n = 750) aged ≥ 50 years who underwent major noncardiac surgery were eligible for the study. Postoperative cardiac troponin-I data were collected retrospectively and consecutively. The primary outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 44 publications
0
27
0
3
Order By: Relevance
“…This is a novel finding differs from the one found by Javed et al and Haddad et al where sepsis was the most common trigger. Elevation in troponin I can occur after noncardiac surgery in patients without CAD (24). In a study by Gualandro et al (25), nearly 50% of patients with postoperative acute coronary syndrome had no evidence of plaque rupture.…”
Section: Discussionmentioning
confidence: 97%
“…This is a novel finding differs from the one found by Javed et al and Haddad et al where sepsis was the most common trigger. Elevation in troponin I can occur after noncardiac surgery in patients without CAD (24). In a study by Gualandro et al (25), nearly 50% of patients with postoperative acute coronary syndrome had no evidence of plaque rupture.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have utilised serial high‐sensitivity troponin assays postoperatively, examining the link between postoperative troponin rise and risk of 30‐day as well as long‐term mortality and MACE . The exact methodology and assays used varies among these studies, but certain themes occur consistently: troponin rises are common (occurring in 10–15% of patients over 45 with in‐patient surgery); only a minority of patients met the universal definition of MI; and clinically silent troponin rises, which were non‐diagnostic of MI, still conferred significant increases in mortality risk.…”
Section: Myocardial Insult Ischaemia and Infarctionmentioning
confidence: 99%
“…In a retrospective study of 750 patients who underwent major noncardiac surgery, Kim, et al reported that the cTnI level at postoperative day 1-2 was significantly correlated with all causes of death after surgery, and cTnI elevations predicted death in a dose-related manner. 2) Moreover, analysis of several years of follow-up revealed that this significant relationship between postoperative cTnI level and mortality disappeared after 6 months of major noncardiac surgery. This prediction of death based on cTn elevations was consistent with previous studies.…”
Section: Cardiac Troponin As a Specific And Non-specific Biomarker Fomentioning
confidence: 98%
“…3,4) The operative mortality of 4.1% in the study population by Kim, et al was relatively high in comparison with previous studies. 2) This may be attributed to their study limitations that included a small sample size, a single center trial, and retrospective design, amongst others. Importantly however, the facts reported by Kim, et al were the first published data from Korea, included a long period of follow-up, and were consistent with several previous reports.…”
Section: Cardiac Troponin As a Specific And Non-specific Biomarker Fomentioning
confidence: 99%